Reducing Academic Mismatch through an Academic Alignment Model - Adam, Syafryanto; Eriyanti, Ribut Wahyu; Sunaryo, Hari (Darul Yasin Al Sys, 2026)
Although the transition from secondary to higher education has been widely studied, comprehensive systemic frameworks integrating personal, curricular, institutional, and policy alignment remain underdeveloped. This study develops and empirically tests the Academic Alignment Model (AAM) as a framework for reducing academic mismatch during the transition to higher education. A sequential explanatory mixed-methods design was employed, involving 420 secondary school students, first-year university students, and key educational stakeholders selected through purposive sampling. Quantitative data were collected using structured questionnaires and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM), while qualitative data from semi-structured interviews were analyzed thematically. The quantitative and qualitative findings were subsequently integrated through joint displays. The results demonstrate that academic alignment operates as a multidimensional mechanism comprising personal, curricular, institutional, and policy alignment, all of which significantly influence academic success and graduate readiness. These findings indicate that reducing academic mismatch requires systemic coherence among students’ educational choices, curriculum structures, institutional support, and education policies. The AAM extends transition and alignment literature by providing an integrated framework for explaining academic mismatch across multiple educational levels. Practically, the findings highlight the need for schools, universities, and policymakers to strengthen career guidance, school–university articulation, institutional support, and policy-monitoring systems.